2017
DOI: 10.1039/c7ee02288c
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic perovskite/silicon-homojunction tandem solar cell with over 22% efficiency

Abstract: An innovative design for a monolithic perovskite/silicon tandem solar cell, featuring a mesoscopic perovskite top subcell and a high-temperature tolerant homojunction c-Si bottom subcell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
186
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(188 citation statements)
references
References 38 publications
2
186
0
Order By: Relevance
“…In recent years, significant advances in lab‐scale multijunction PCE have been reported, abundantly for perovskite‐Si and modestly for perovskite‐CIGS multijunction solar cells . The prospect of scalable high‐efficient perovskite‐Si and perovskite‐CIGS multijunction solar modules holds substantial potential for a disruptive change in the PV market .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant advances in lab‐scale multijunction PCE have been reported, abundantly for perovskite‐Si and modestly for perovskite‐CIGS multijunction solar cells . The prospect of scalable high‐efficient perovskite‐Si and perovskite‐CIGS multijunction solar modules holds substantial potential for a disruptive change in the PV market .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a textured anti-reflection (AR) foil featuring pyramidal features enhances the light harvesting ability of monolithic silicon/perovskite tandem devices 17,22 due to the enhanced anti-reflection from the front and enhanced light trapping in the Si cell. Other work has shown that texturing that replicates the surface of a rose petal has even better anti-reflection properties.…”
Section: Further Optimizationmentioning
confidence: 99%
“…4,31 Parasitic absorption of short wavelength light also exists in the ITO/MoO 3 stack, which is also the most commonly used transparent conductive stack for the top of the semi-transparent perovskite in a tandem. 17,32 The thin MoO 3 protects the perovskite cell from sputter damage from the deposition of ITO, which is responsible for electrical conduction. Absorption in the ITO/MoO 3 /HTM stack hinders the effectiveness of the use of the high bandgap perovskite.…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The parasitic absorption by 50 nm PTAA HTM, mostly occurring in the blue region, contributes to a current loss of ≈1.16 mA cm −2 . Thanks to the use of a much thinner film, this is substantially diminished compared to ≈2.7 mA cm −2 arising from ≈100 nm Spiro‐OMeTAD in our previous tandem design . The next most significant losses in order of importance stem from the MoO x buffer layer (≈0.76 mA cm −2 ), the front IZO contact layer (0.72 mA cm −2 ), and the metal on the rear side of the Si cell (≈0.62 mA cm −2 ).…”
Section: Optical Modeling and Optimizationmentioning
confidence: 86%